1999
DOI: 10.1002/1529-0131(199908)42:8<1691::aid-anr18>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of early seropositive rheumatoid arthritis with minocycline: Four-year followup of a double-blind, placebo-controlled trial

Abstract: Among patients with seropositive RA, remissions are more frequent and the need for DMARD therapy is less in those treated early in the disease course with minocycline compared with those treated with conventional therapy delayed by an average of only 3 months. Minocycline appears to be an effective therapy for early RA; further investigation into its mechanism of action is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(44 citation statements)
references
References 22 publications
1
41
0
1
Order By: Relevance
“…Recently, randomized doubleblind, placebo-controlled trials have demonstrated the efficacy of minocycline in improving the clinical parameters of RA (106)(107)(108)(109). Importantly, one trial showed long-term benefit of minocycline and a decrease in radiographic progression in a subset of patients who were positive for the HLA shared epitope (HLA-DR4ϩ) (110).…”
Section: Pharmacologic Treatment Of Ramentioning
confidence: 99%
“…Recently, randomized doubleblind, placebo-controlled trials have demonstrated the efficacy of minocycline in improving the clinical parameters of RA (106)(107)(108)(109). Importantly, one trial showed long-term benefit of minocycline and a decrease in radiographic progression in a subset of patients who were positive for the HLA shared epitope (HLA-DR4ϩ) (110).…”
Section: Pharmacologic Treatment Of Ramentioning
confidence: 99%
“…This change in treatment philosophy was not based on direct comparisons of the efficacy of these strategies, but rather was motivated by the recognition that joint damage occurs early in RA, that the health outcomes of patients treated using the previous strategy were generally poor, and that diseasemodifying medications were safer than previously thought (5)(6)(7)(8)(9)(10). Recently, the findings from several short-term controlled trials and observational studies have suggested that treatment with disease-modifying medications initiated early in the course of RA leads to improved control of joint inflammation, less joint damage, and better health compared with the outcomes following even short delays in treatment (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Furthermore, genetic analyses and transmission in animals indicate that arthritis is not directly linked to genetic abnormalities [22] showed greater improvements in joint swelling and tenderness (p<0.02), and the treatment group also had better improvements in hematocrit, SED rate, platelet counts and rheumatoid factor with no serious toxicity [27,28]. A 4-year follow-up indicated that the minocycline-treated patients had fewer relapses and less frequent need for immune-suppressive drugs to control their RA (p<0.02) [29]. Although treatment of arthritis with antibiotics was effective and safe, treatment failures can, just as in any treatment for arthritis, be due to therapeutic failures, resistance and/or mutation of the microorganism [30].…”
Section: Letter To Editormentioning
confidence: 99%